2012
DOI: 10.1080/09540121.2012.661839
|View full text |Cite
|
Sign up to set email alerts
|

Child and young adult-headed households in the context of the AIDS epidemic in Zimbabwe, 1988–2006

Abstract: The emergence of Child-Headed Households (CHH) and Young Adult Households (YAH) has largely been taken as an indicator of the erosion of the traditional safety nets in sub-Saharan countries and a direct consequence of the increasing number of orphans in the region. However, the initial evidence presented so far suggests that the process of formation of CHH and YAH is more complex than it appears to be. Using the four available waves of the Zimbabwe Demographic and Health Surveys (1988, 1994, 1999, and 2005/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It is thought that fewer than five per cent of orphans live on the streets or in institutions although this has increased in the most severely affected countries (Monasch and Boerma 2004; Powell et al 2004; Beard 2005; United Nations Children’s Fund 2005; UNICEF, UNAIDS, and PEPFAR 2006; Morantz and Heymann 2010). Furthermore, a recent study of child-headed households in Zimbabwe found that few of these households comprised orphans, which challenges the idea that such households reflect the absorptive capacity of the extended family (Ciganda et al 2010). Instead, the extended family system characteristic of the region has shown a remarkable capacity to absorb orphans and mitigate the consequences of there being so many newly orphaned children (Caldwell 1997; Monasch and Boerma 2004; Hosegood et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…It is thought that fewer than five per cent of orphans live on the streets or in institutions although this has increased in the most severely affected countries (Monasch and Boerma 2004; Powell et al 2004; Beard 2005; United Nations Children’s Fund 2005; UNICEF, UNAIDS, and PEPFAR 2006; Morantz and Heymann 2010). Furthermore, a recent study of child-headed households in Zimbabwe found that few of these households comprised orphans, which challenges the idea that such households reflect the absorptive capacity of the extended family (Ciganda et al 2010). Instead, the extended family system characteristic of the region has shown a remarkable capacity to absorb orphans and mitigate the consequences of there being so many newly orphaned children (Caldwell 1997; Monasch and Boerma 2004; Hosegood et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In SSA, the magnitude of the HIV/AIDS crisis has eroded familial networks which traditionally cared for OVC [ 14 ] and has posed heightened economic and social risks to households [ 15 ]. Among families that support OVC in economically poor communities, some of the most common unmet needs include education, food, medical care and clothing [ 16 ] as well as a lack of birth certificates which poses a barrier to accessing school enrollment and health services [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of CHHs and YHHs is a direct consequence of the increasing number of orphans as well as the erosion and dismantling of the social support system for orphans and families by the scourge of HIV/AIDS [4,6,10]. Literature suggests that older age is presently the criteria for assuming the parenting role in the household affected by HIV/AIDS [11].…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that older age is presently the criteria for assuming the parenting role in the household affected by HIV/AIDS [11]. Ciganda et al [6] argued that, many households that start as child-headed change their status when the head turns 18 years old, without qualitatively changing their situation. This observation is supported by Popoola and…”
Section: Introductionmentioning
confidence: 99%